Remediation of Cr(VI)/Cd(ІІ)-Contaminated Groundwater with Simulated Permeable Reaction Barriers Filled with Composite of Sodium Dodecyl Benzene Sulfonate-Modified Maifanite and Anhydride-Modified Fe@SiO2@Polyethyleneimine: Environmental Factors and Effectiveness. (9th November 2021) - Gao, Jingqing; Zhai, Yalin; Huang, Zhenzhen; Ren, Peng; Gao, Jianlei; Chen, Zhijun; Li, Shunling
Abstract : A composite material of sodium dodecyl benzene sulfonate- (SDBS-) modified maifanite and anhydride-modified Fe@SiO2 @PEI (PEI) was used as an adsorbent for the removal of hexavalent chromium (Cr(VI)) and bivalent cadmium (Cd(II)) from groundwater by using column experiments and simulated PRB test. In this study, the optimum proportion of SDBS-modified maifanite and anhydride-modified Fe@SiO2 @PEI was 5 : 1. In the column experiments, it was found that the penetration time increased with the increase of the initial concentrations (30, 60, and 90 mg/L) and the decrease of the flow rates (5.45, 10.9, and 16.35 mL/min) at an influent pH of 6.5 ± 0.3 . It was also obtained that the removal rates of Cr(VI) and Cd(ІІ) reached 99.93% and 99.79% at an initial Cr(VI) and Cd(ІІ) concentration of 30 mg/L with the flow rate of 10.9 mL/min, respectively, at 6 h. Furthermore, excellent removal effectiveness of Cr(VI) and Cd(ІІ) (85.94% and 83.45%, respectively) was still achieved in simulated PRB test at a flow rate of 5.45 mL/min with the heavy metal solution concentration of 5.0 ± 0.5 mg/L (Cr(VI) and Cd(II) concentration were, respectively, 5.0 ± 0 . 5 mg/L); and the adsorbent had not completely failed by the end of the trial. Yoon-Nelson model was successfully applied to predict the breakthrough curves for the assessment of composite material heavy metal removal performance and was in good agreement with the experimental data of the heavy metal removal efficiency. The strong removal ability of the adsorbent could be attributed to the fact that maifanite with a large diameter can provide support and increase the permeability coefficient and porosity and that zero-valent iron (ZVI) can convert Cr(VI) to Cr(III) and improve the adsorption capacity of maifanite. The obtained results suggested that the novel PRB fillers have great significance for preventing and controlling Cr(VI)/Cd(ІІ)-contaminated groundwater.